Differences in pressure pain sensitivity of elite male soccer players on artificial turf and natural grass - Dominguez-Martin, M. A.; Lopez-Ruiz, F.; Reyes-Lopez, M. V.; Valenza, G.; Fernandez De Las Penas, C.; Madeleine, P. (Sports Technology, 2013)
The aim of this study was to compare topographical pressure pain sensitivity maps of the lower extremity in elite footballers (soccer) playing on artificial turf or natural grass. A total of 16 football players (mean age ± SD: 22 ± 2 years) for artificial turf and 13 football players (age: 22 ± 3 years) for natural grass participated. Pressure pain thresholds (PPTs) were measured bilaterally over 23 locations of the lower extremity to assess deep structure sensitivity to mechanical pain. The analysis of variance detected significant differences in PPT between groups and measurement points (P < 0.001). Football players playing on natural grass exhibited lower PPT as compared to those playing on artificial turf (P < 0.05). In addition, PPT over vastus medialis muscle had the lowest value (most sensitive) (P < 0.01); whereas PPT over the rectus femoris was the highest one (least sensitive). This study showed the ability of PPT maps to reveal heterogeneous distribution of mechanical sensitivity in relation to turf type. The decreased mechanical sensitivity to pain among football players playing on artificial turf compared with natural grass points most likely towards a favourable trait of such turf type. Further studies are needed to confirm these findings.